STRATEGI PENINGKATAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDIT AL-HUSNA LEBONG SELATAN - Apriliandi Apriliandi (IAIN Bengkulu, 2019)
This study aims to determine; (1) the competence of Islamic religious teacher administration in SDIT Al-Husna, South Lebong. (2) the process of improving the quality of Islamic religious education learning at SDIT Al-Husna Selatan Lebong, (3) the results of the implementation of the strategy to improve the quality of learning in Islamic religious education at SDIT Al-Husna Lebong Selatan. The existence of this research is expected to improve the quality of learning in Islamic religious education in SDIT Al-Husna, South Lebong. This study uses a type of experimental research. The sample in the study was all first grade students of SDIT Al-Husan Lebong Selatan in the 2018/2019 academic year consisting of 2 classes with a total of 17 IA class students and 17 class I B students. Data was collected by observation, interviews, documentation and results tests study in multiple choice. The collected data is processed qualitatively and quantitatively. The results showed that: (1) the administrative completeness of Islamic education teachers at Al-Husna Lebong Selatan SDIT was at a percentage of 61.25%, meaning that the complete administrative documents for learning Islamic education teachers at SDIT Al-Husna Lebong Selatan were incomplete. (2) the process of improving the quality of Islamic education learning in the Al-Husna South Lebong SDIT by completing the Islamic education teacher teaching administration to 87.5%. Then in the learning process carried out with 3 meetings by applying the strategy to improve the quality of learning in the experimental class and expository strategy in the control class. (3) the results of the implementation of the strategy to improve the quality of learning Islamic education in SDIT Al-Husna Selatan Lebong in the experimental class there were average learning outcomes, 77.05, 81.17 and 85.88 and in the control class there were an average of 75.88 , 77.05 and 77.94. This means that the implementation of the quality improvement strategy in the experimental class was more successful in improving the quality of Islamic education learning in SDIT Al-Husna in the South rather than the expository strategy in the control class.